Experimental AC loss analysis of braid type non-inductive coil for superconducting fault current limiter. (June 2020) - Song, W; Pei, X; Xi, J; Xiang, B; Liu, Z
Abstract: Resistive superconducting fault current limiter (SFCL) plays a key role to realise the stability and safety of power grid and the future electric aircraft. This paper presents the design and test of a braid type non-inductive coil for SFCL. One inner coil and one outer coil were wound around a G10 tube using 4 mm-wide SuperPower wires. Two configurations of the braid type non-inductive coil were achieved by connecting the inner coil and outer coil in series and in parallel, respectively. AC loss results of these two non-inductive coils were measured and compared to investigate the AC loss dependency on coil configuration and current distribution. It has been concluded that braid type non-inductive coil has low AC loss due to magnetic field cancellation. Serial connection of the inner and outer coils leads to a good degree of field cancellation, which results in higher critical current and lower AC loss of the non-inductive coil, compared to parallel connection.